Maetro Tenun Songket Bungo Tanjung Dalam Fotografi Dokumenter - diansyah, Muhamad Nur (Matalensa: Journal of Photography and Media, 2022)
The scription of this work is entitld “Songket Weaving MaestroBungo Tanjung in documentery photography”. The purpose of this thesis is to create documentery photography of songket woven fabric craftsmen of Bungo Tanjung. The data collection method used is:observation, study of literature, and interview. From the results of the study it is known that the number of songket woven fabric craftsmen has been much reduced.songket cloth is currently less attractive to the younger generation in Muara Bungo as a successor, this is due to the declining public interest in traditional songket woven fabrics starting from the many songket motifs and patterns circulating in the more modern market,the songket woven fabric in question is the songket woven cloth of bungo cape and the songket craftsmen who are still active and survive until now. Documentary presentation of works with story photo techniques, photo series consisting of more than one photo that tells abaut an incident where there is an explanatory prefix, story and cover. Documentary photos can play a role in this traditional art because documentary carris out data collection activities, archive, edit and present this traditional art in archive form. Documentary photography can provide a clearer nuance in drawing conclusions from a research, and create images that aim to present social reality through the point of view of visual truth and honesty.